PENGARUH KONSENTRASI DAN FREKUENSI APLIKASI ISOPROTHIOLANE TERHADAP PERTUMBUHAN DAN HASIL CABAI MERAH KERITING (Capsicum annum L) - Kumala, Istiglaila Risma; Santosa, Sartono Joko; Hardiatmi, JM Sri (Innofarm:Jurnal Inovasi Pertanian, 2013)
The of research "INFLUENCE CONCENTRATION AND FREQUENCY APPLICATIONS ISOPROTHIOLANE ON THE GROWTH AND YIELDÂ  the curly red chili (Capsicum annuum L.)" has been done on 6th Apriluntil14th July 2013 in Green House of Agriculture Faculty SlametRiyadi University which is located in Kadipiro Village, Banjarsari district, Surakarta regency, Central Java province. This research aims to known the concentration and frequency application theÂ  isoprothiolane that can improve crop growth and the yield of curly red chili optimally This research arranged was Completely Randomized Design (CRD), The results show that giving : Isoprothiolanein pepper red curly significant effect on increas thenumber of fruits per crop, length of fruit, diameter of fruit, weight of fruit per crop, but did not significantly effect height of plant, the fresh weight of biomass and the dry weight of biomass. Giving isoprothiolane with concentration 0.4 ml / l of water and 2 times theapplicationgivesthe highest result on the number offruitspercropis13.67, length of fruit is14.33cm, diameter of fruitis6.84mm, andweight offruitpercropis 25.20g. Key words :concentration, frequency application, curly red chili